Development of Stochastic Voronoi Lattice Structures via Two-Photon Polymerization. (2nd January 2022) - Goodwin, Lynne A.; Schmidt, Derek W.; Kuettner, Lindsey; Patterson, Brian M.; Walker, Ethan; Edgar, Alex; Morrow, Tana; McCreight, Cayleigh; Harris, Jonathan A.; Herrmann, Hans; Scheiner, Brett; Schmitt, Mark J.
Abstract: Low-density polymer foams of varying sizes, shapes, and densities are of specific interest to the inertial confinement fusion (ICF) program and related high-energy density plasma physics research. Historically, these foams are comprised of polystyrene or other low atomic number materials and have densities in the 30 to 300 mg/cm 3 range. However, at the lower end of this density range, these traditional polymer foams become fragile and difficult to cast and machine into the geometries needed. Recently, the need by experimentalists for materials with densities below 30 mg/cm 3 has increased. To address these needs, we are developing three-dimensional (3-D) printing techniques to create high-precision, low-density, and repeatable complex lattice structures. Using two-photon polymerization 3-D printing, we recently developed the first 5 mg/cm 3 low-density lattice structure having an annular hemispherical shape. These microscale to mesoscale structures were modeled and designed using the nTopology software, specifically utilizing the "Voronoi volume lattice" and "random points in body" option blocks. All printing operations were performed using the Nanoscribe Photonic Professional GT instrument. Characterization of these 3-D structures was conducted using various microscopic and X-ray tomographic imaging techniques. Overall printed part sizes ranged from 1 to 5 mm in diameter and were composed of lattice ligaments having thicknesses in the 3- to 5-µm range. These structures have been incorporated into ICF targets recently shot on both the University of Rochester's Laboratory of Laser Energetics Omega laser and the National Ignition Facility.